PENGUATAN KLASTER PANGAN OLAHAN BERBASIS MOCAF DI KABUPATEN BLITAR - Sidik, Muhammad Ansorudin (Badan Pengkajian dan Penerapan Teknologi, 2011)
As its food diversification effort, Blitar develops modified cassava flour (mocaf) using cassava as raw material. Mocaf is considered as one of agricultural commodities with good prospect for development. Sari Raos food processing cluster is one of Putri Kencana programs. A study on this cluster, using Porter’s Four Diamond Framework, has been conducted for two years. The result shows that mocaf based food processing industrial cluster in Blitar canbe synergized with in the Sourthern region of Java. Strategies to develop/strengthen the cluster can be implemented with the programs of Blitar local government.